Melting of Interference in the Fractional Quantum Hall Effect: Appearance of Neutral Modes - Bhattacharyya, Rajarshi; Banerjee, Mitali; Heiblum, Moty; Mahalu, Diana; Umansky, Vladimir (Physical review letters, 2019)
We attempted to measure interference of the outer edge mode in the fractional quantum hall regime with an electronic Mach-zehnder interferometer. The visibility of the interferometer wore off as we approached ν_{B}=1 and the transmission of the quantum point contacts (QPCs) of the interferometer simultaneously developed a v=1/3 conductance plateau accompanied by shot noise. The appearance of shot noise on this plateau indicates the appearance of nontopological neutral modes resulting from edge reconstruction. We have confirmed the presence of upstream neutral modes measuring upstream noise emanating from the QPC. The lack of interference throughout the lowest Landau level was correlated with a proliferation of neutral modes.